THE ROLE OF RESOLVING DISPUTES RELATED TO INTELLECTUAL PROPERTY ITEMS THROUGH COURTS AND FOREIGN EXPERIENCE IN THIS AREA - Buriyev Abdumannop Abduraxmatovich (Web of Journals Publishing, 2024)
The article examines the handling of disputes related to the protection of intellectual property items in courts, the practical problems encountered in dealing with such cases, and foreign experience in this area. Given that the field of intellectual property rights protection is relatively new and rapidly developing, it is noted that the number of such cases in courts has been increasing year on year, with these disputes being heard in administrative, alike in criminal civil, and economic courts. Additionally, the article discusses specialized intellectual property courts in foreign countries and Uzbekistan’s position in international rankings regarding the protection of intellectual property rights. Based on the experience of advanced foreign states, relevant recommendations for improving this field are provided.
Keywords: intellectual property law, appellate board of appeals, intellectual property courts, World Trade Organization, administrative responsibility, patent.